2013
DOI: 10.4236/ojtr.2013.12009
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient rehabilitation outcomes in solid organ transplantation: Results of a unique partnership between the rehabilitation hospital and the multi-organ transplant unit in an acute hospital

Abstract: Objective: To determine the outcomes in solid organ transplant recipients following inpatient rehabilitation, as a result of a unique partnership between the rehabilitation hospital and the multiorgan transplant program in an acute hospital. Design: Retrospective observational study. Setting: Community rehabilitation hospital affiliated with a university. Participants: A cohort of 173 organ transplant patients admitted consecutively over a four-year period (2004-2008) was compared to a cohort of all rehabilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 56 publications
1
33
0
5
Order By: Relevance
“…Consistent with previous studies, medical complications during rehabilitation were common among heart and/or lung transplant recipients, affecting 33% of admissions in the present study and typically 20% to 40% of reported admissions . The majority of observed complications were respiratory in nature (including infections, pleural effusions, and acute respiratory distress), and although there appeared to be a slightly higher incidence of complications among lung compared to heart transplant recipients, this difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, medical complications during rehabilitation were common among heart and/or lung transplant recipients, affecting 33% of admissions in the present study and typically 20% to 40% of reported admissions . The majority of observed complications were respiratory in nature (including infections, pleural effusions, and acute respiratory distress), and although there appeared to be a slightly higher incidence of complications among lung compared to heart transplant recipients, this difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 89%
“…Patcai et al also report seminal data but from a mixed cohort of solid organ transplant recipients receiving inpatient rehabilitation, including 56 heart/lung transplant patients. They observed functional gains postrehabilitation, but improvements were more modest, required longer lengths of stay, and were associated with higher complication rates among transplant patients compared to general rehabilitation patients . Later work by Gupta et al in a small cohort of exclusively heart transplant recipients supported earlier findings that inpatient rehabilitation can lead to functional benefits after transplantation …”
Section: Introductionmentioning
confidence: 80%
“…Outcome data are limited with respect to LTs as a population; nevertheless, the increasing frequency of LT and the changing demographics of acute rehabilitation necessitate a comparison with other rehabilitation populations. Progress of LT Functional Independence Measure score gains has been found to be slower than other populations and is more in line with Functional Independence Measure gains seen in stroke patients [36,37]. Although exercise capacity and skeletal muscle function are expected to improve with exercise, therapy after transplantation studies indicate LT recipients do not reach predicted levels in maximal exercise capacity or skeletal muscle strength [35].…”
Section: Rehabilitation Outcomes After Ltmentioning
confidence: 89%
“…Hospital readmission rates in patients undergoing LT have been documented as high as 19%‐40% of total acute rehabilitation admissions [24,36,37]. Such findings warrant special considerations and close surveillance for LT patients, because they tend to have high complications rates [42‐45], slower functional gains, and more readmissions compared with other acute rehabilitation populations [24,36,37].…”
Section: Rehabilitation Outcomes After Ltmentioning
confidence: 99%
“…This likely occurs through around-the-clock interaction with health professionals, close monitoring of medications, easy access to diagnostics, and therapies to combat deconditioning. (27)…”
Section: Discussionmentioning
confidence: 99%